Chapelwood - Priest, Cherie (Priest, Cherie. Borden dispatches., 2015)
Birmingham, Alabama is infested with malevolence. Prejudice and hatred have consumed the minds and hearts of its populace. A murderer, unimaginatively named "Harry the Hacker" by the press, has been carving up citizens with a hatchet. And from the church known as Chapelwood, an unholy gospel is being spread by a sect that worships dark gods from beyond the heavens. This darkness calls to Lizzie Borden. It is reminiscent of an evil she had dared hoped was extinguished. The parishioners of Chapelwood plan to sacrifice a young woman to summon beings never meant to share reality with humanity. An apocalypse will follow in their wake which will scorch the earth of all life. Unless she stops it ...